REKONSTRUKSI HUKUM WARISAN DI INDONESIA PERSPEKTIF PLURALISME AGAMA - Abdul Mufid (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2020)
Juridical, theological, and philosophical differences in religion are one of the challenges for someone to become an heir. On the other hand, empirically historical-sociological is not the case, because there are reasons (illat) or other related to different religions to get the inheritance of Muslims who inherit using welfare factors. This research uses the normative legal research method. The author uses Gustav Radburch's theory of legal objectives governing justice, expediency, and legal certainty. Based on the results of the research found in the compilation of Islamic law is not available to the heirs who have been given apostasy. Religious differences as a barrier to inherit are specifically intended for heirs. So it can be concluded that Muslim heirs can inherit the assets of non-Muslim heirs, but not vice versa. In this study, non-Muslim heirs cannot inherit wealth from Muslim heirs, in order to fulfill a sense of justice and respect, these non-Muslim experts still obtain inheritance through mandatory wills which are processed through court determination. The will is obliged to be determined as a way out of giving the inheritance to non-Muslim heirs because the heir has died, and there is no other way to be able to transfer the heir's assets to the non-Muslim heirs.